Structural geometry and timing of deformation in the Chainat duplex, Thailand - Smith M. (2014)
The Chainat duplex is about 100 km in a north-south direction, and was developed along the predominantly sinistral Mae Ping fault zone, which was active during the Cenozoic. The duplex is manifested as eroded, north-south- and NW-SE-striking outliers of Palaeozoic and Mesozoic rocks rising from the surrounding flat plains of the Central Basin (a Pliocene-Recent post-rift basin). Satellite images, geological maps and magnetic maps have been used to reconstruct the structural geometry of the duplex, which is composed of a series of north-south-striking ridges, bounded to the north and south by NW-SE-striking faults. Overall, the duplex has the geometry of analogue restraining-bend models with relatively low displacement. No well-developed duplex-traversing short-cut faults linking the principal displacement zones are apparent. The duplex shows evidence for widespread sinistral motion, as well as some dextral reactivation the latter of which is particularly marked in the eastern part of the duplex. The main sinistral activity ended at about 30 Ma: subsequently, minor, episodic reactivation of the duplex may have occurred. Detailed timing of events cannot be determined from structures within the duplex, but the evolution of adjacent rift basins suggests that stresses developed during episodes of inversion may have also caused reactivation of strike-slip faults (sinistral for NW-SE to north-south striking faults) during the Miocene. Minor episodic dextral motion may also have been of Late Oligocene-Miocene and/or Pliocene-Recent age. © The Geological Society of London 2007.